Penambahan Carboxymethyle Cellulosa (CMC) Dan Lama Penyimpanan Pada Suhu Dingin Terhadap Karakteristik Susu Kacang Merah - Richard Randi; I Wayan Sudiarta; I Nyoman Rudianta (GEMA AGRO, 2022)
Local nuts are an alternative source of vegetable protein that is cheap and affordable by the people of Indonesia. Peanuts whose potential has not been fully explored, including red beans, green beans, and cowpeas are types of beans that have the potential to be developed in various products of the food industry (Fachrudin, 2009). One type of legume that is very good for consumption is red beans. This study aims to determine the addition (CMC) and storage time at cold temperature to the characteristics of red bean milk. The research design used a completely randomized design (CRD) factorial pattern with two factors and two replications, namely factor I was the addition of CMC treatment consisting of 4 levels, namely: (0.04%), (0.06%), (0.08 %), (0.10%). Factor Il is the treatment of shelf life which consists of 4 levels, namely: 0 days, 3 days, 6 days, and 9 days. Observations were carried out objectively including: moisture content, ash content, fat content, protein content, carbohydrates, viscosity, pH and color. Meanwhile, subjective observations include: color, aroma, taste, texture and overall acceptance. The best research results were obtained in the treatment with the addition of 0.06% CMC and storage time on day 3, with the results of 91.82% moisture content, 0.64% ash content, 1.92% fat content, 3.09 protein content. %, carbohydrate content of 2.73%, viscosity 29.75%, pH level of 6.57%, and subjectively have the highest preference for panelists